New Thermophilic α/β Class Epoxide Hydrolases Found in Metagenomes From Hot Environments - Ferrandi, Erica Elisa; Sayer, Christopher; De Rose, Simone Antonio; Guazzelli, Elisa; Marchesi, Carlotta; Saneei, Vahid; Isupov, Michail N.; Littlechild, Jennifer A.; Monti, Daniela (Frontiers in Bioengineering and Biotechnology, 2018)
Two novel epoxide hydrolases (EHs), Sibe-EH and CH65-EH, were identified in the metagenomes of samples collected in hot springs in Russia and China, respectively. The two α/β hydrolase superfamily fold enzymes were cloned, over-expressed in Escherichia coli, purified and characterized. The new EHs were active towards a broad range of substrates, and in particular, Sibe-EH was excellent in the desymmetrization of cis-2,3-epoxybutane producing the (2R,3R)-diol product with ee exceeding 99%. Interestingly these enzymes also hydrolyse (4R)-limonene-1,2-epoxide with Sibe-EH being specific for the trans isomer. The Sibe-EH is a monomer in solution whereas the CH65-EH is a dimer. Both enzymes showed high melting temperatures with the CH65-EH being the highest at 85°C retaining 80% of its initial activity after 3 h thermal treatment at 70°C making it the most thermal tolerant wild type epoxide hydrolase described. The Sibe-EH and CH65-EH have been crystallized and their structures determined to high resolution, 1.6 and 1.4 Å, respectively. The CH65-EH enzyme forms a dimer via its cap domains with different relative orientation of the monomers compared to previously described EHs. The entrance to the active site cavity is located in a different position in CH65-EH and Sibe-EH in relation to other known bacterial and mammalian EHs.